2023
DOI: 10.3389/fpubh.2023.1228010
|View full text |Cite
|
Sign up to set email alerts
|

Perception of consanguineous marriage among the qatari population

Yasamin Abdu,
Khalid Ahmed,
Mohamed Izham Mohamed Ibrahim
et al.

Abstract: BackgroundHereditary blood diseases are widespread among the Arab population due to the high rates of consanguineous marriages; research regarding the perception of consanguineous marriage in some countries, such as Qatar, is extremely scarce. Therefore, this study aimed to investigate the prevalence of consanguineous marriage and assess the perception of consanguineous marriage among the Qatari population.MethodsA cross-sectional study used a self-administered questionnaire among 395 Qatari adults aged 18–35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…Studies from Turkey & Iran had the impression that in the premarital stage, the opinions are not mature enough compared to the mature age when one faces the hardships of life ( 26 , 27 ). Our findings regarding community attitude are similar to those of a Qatari study that reported a similar attitude to this aspect of the determinant ( 28 ). In contrast, while taking the opinion of parents agreeing with the CM of their children, a Pakistani study pointed out that cultural continuity and wealth safety are considered important factors when deciding their children’s marriages ( 29 ).…”
Section: Discussionsupporting
confidence: 90%
“…Studies from Turkey & Iran had the impression that in the premarital stage, the opinions are not mature enough compared to the mature age when one faces the hardships of life ( 26 , 27 ). Our findings regarding community attitude are similar to those of a Qatari study that reported a similar attitude to this aspect of the determinant ( 28 ). In contrast, while taking the opinion of parents agreeing with the CM of their children, a Pakistani study pointed out that cultural continuity and wealth safety are considered important factors when deciding their children’s marriages ( 29 ).…”
Section: Discussionsupporting
confidence: 90%